(untitled) (International Journal of Physiotherapy, 2015)
Background: DRX9000 spinal decompression is slightly known for treating chronic lumbar disc prolapse. The aim of the study was to examine the effectiveness of DRX9000spinal decompression on pain in chroniclumbar disc prolapse (CLDP). Methods: twenty male subjects with chronic lumbar disc prolapse,aged between 40:60 years were included in the study. They were assessed forpain intensity byslump test,straight leg raising test (SLR),modified Oswestery questionnaire (OQ) and visual analogue scale (VAS). The study continued forsix weeks, the 20 patients were equally divided into two groups. Group A (experimental) received spinal decompression, stability and McKenzie exercises; and ice, at a rate of 3 days per week, the duration of each session was 60 minutes. While group B (control) were treated by exercises and ice only. Results: Majority of patients had positive findings in reducing pain clinically; however, statistically there was no significant difference. Conclusion: It can be concluded that spinal decompression has an effect, but not statistically significant in decreasing pain on patients with lumbar disc prolapse. This may be due to limited number of patients. We can recommend increasing the sample size to generalize the results, MRI scan follow up should be done after one year to determine if the effects are permanent or transient, comparing the effects of decompression between acute & chronic cases of lumbar disc prolapse, also male & female patients.